Ghetto Symphony - Mavolwane, Mandhla A. (Book collections on Project MUSE., 2019)
Ghetto Symphony is an orchestra of short stories and poems which vividly portray the socio-economic situation affecting teens and young adult groups across Zimbabwe. It is a compilation of an underground poet's readings and writings which highlight the restrictions faced daily by the masses, and also project innovative ideas to overcome the dark cloud hovering over the future of Zimbabwe.